2020
DOI: 10.3389/fbioe.2020.00997
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles: Opportunities and Challenges for Clinical Translation

Abstract: Extracellular vesicles (EVs), including exosomes and microvesicles, derived from mesenchymal stem/stromal cells (MSCs) exert similar effects as their parental cells, and are of interest for various therapeutic applications. EVs can act through uptake by the target cells followed by release of their cargo inside the cytoplasm, or through interaction of membrane-bound ligands with receptors expressed on target cells to stimulate downstream intracellular pathways. EV-based therapeutics may be directly used as sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 116 publications
(150 reference statements)
0
98
0
Order By: Relevance
“…Recent studies suggested that stem cell-derived factors, called “biomaterials”, could improve the development of preimplantation embryos [ 16 , 17 ]. The secreted factors derived from the stem cells in the medium are referred to as extracellular vesicles [ 18 ]. Therefore, the medium is named the conditioned medium (CM) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that stem cell-derived factors, called “biomaterials”, could improve the development of preimplantation embryos [ 16 , 17 ]. The secreted factors derived from the stem cells in the medium are referred to as extracellular vesicles [ 18 ]. Therefore, the medium is named the conditioned medium (CM) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite intense research of EVs in wound healing, only mesenchymal stem cell‐derived EVs (MSC‐EVs) have been studied and shown to make a positive contribution to wound healing 27‐32 . EVs isolation from MSCs has some of drawbacks: culture and expansion of MSCs, which could take several days or weeks; red blood cell contamination during isolation; limited cell viability and neovascularization capacity, and isolation of MSCs from bone marrow is highly invasive 33‐35 . So, identifying other potential cell‐derived pro‐wound healing EVs is urgently required for feasible utilization of EV therapy to accelerate wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Because different protocols for purification of EVs may lead to different results, including the purity and yield, it is critical to define the standard isolation of EVs as described above and it needs to be recognized that it is likely that each MSC-EV preparation leads to a different product. The challenges related to the clinical translation of MSC-EVs have also extensively been discussed in a recent article (Maumus et al, 2020 ).…”
Section: Practical Considerations For Ev-based Therapiesmentioning
confidence: 99%